2022
DOI: 10.1186/s12888-022-03854-x
|View full text |Cite
|
Sign up to set email alerts
|

Patient-reported outcomes of lifestyle interventions in patients with severe mental illness: a systematic review and meta-analysis

Abstract: Background Lifestyle interventions for severe mental illness (SMI) are known to have small to modest effect on physical health outcomes. Little attention has been given to patient-reported outcomes (PROs). Aim To systematically review the use of PROs and their measures, and quantify the effects of lifestyle interventions in patients with SMI on these PROs. Methods Five electronic databases were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 83 publications
4
12
0
Order By: Relevance
“…Furthermore, the ACHIEVE study showed 2.5kg (95% CI, -4.1 to -0.8) weight reduction compared with controls after 12 months, and 3.2kg (95% CI, -5.1 to -1.2) after 18 months. We did not find an effect of SMILE on quality of life, in line with results from other lifestyle interventions (27). Finally, research suggests that lifestyle interventions may have positive effects on depression and anxiety severity (27), not measured in this study.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Furthermore, the ACHIEVE study showed 2.5kg (95% CI, -4.1 to -0.8) weight reduction compared with controls after 12 months, and 3.2kg (95% CI, -5.1 to -1.2) after 18 months. We did not find an effect of SMILE on quality of life, in line with results from other lifestyle interventions (27). Finally, research suggests that lifestyle interventions may have positive effects on depression and anxiety severity (27), not measured in this study.…”
Section: Discussionsupporting
confidence: 85%
“…We did not find an effect of SMILE on quality of life, in line with results from other lifestyle interventions (27). Finally, research suggests that lifestyle interventions may have positive effects on depression and anxiety severity (27), not measured in this study. Future researchers should consider more patient-reported outcomes as they are beneficial to people with SMI.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations